The Effect of Snowball Throwing Learning Model on Learning Outcomes Elementary Student Mathematics: Literature Study: Pengaruh Model Pembelajaran Snowball Throwing Terhadap Hasil Belajar Matematika Siswa SD : Studi Literatur - Rindi Isro Ningsih; dian estu prasetyo; ratnawati (International Journal of Technology Vocational Education and Training, 2020)
This research is motivated by the low learning outcomes of elementary school students' mathematics content. The low student learning outcomes are caused by students having difficulty understanding mathematics materials, the lack of variation used in the use of learning models and the need for innovative and fun models in learning mathematics content, the lack of response and enthusiasm of students in learning mathematics so that students' motivation becomes low and interest in learning mathematics students also become low. The purpose of this study was to determine what points are related to the influence of the snowball throwing cooperative learning model on the learning outcomes of elementary school students' mathematics content. This type used the method of the literature study. This study examined 11 article and 1 theses. From several journals that have been studied by the author, the results show that: The snowball throwing type of cooperative learning model has an effect on the effectiveness of student learning, the snowball throwing type cooperative learning model makes students motivated to learn, the snowball throwing type cooperative learning model can make students have interest in learning.